Toll like receptor 2(TLR2) in acne vulgaris patients before and after oral isotretinion therapy - Mahmood, Wakas Saadi (AL-Kindy College Medical Journal, 2019)
Background: Acne vulgaris is one of the top three most commonly encountered dermatological problems worldwide in both primary and secondary care. Human keratinocytes express functional TLR2 heterodimers. An increased expression of TLR2 was detected in the epidermis of inflammatory acne lesions, as observed in normal skin; the expression level increased with the degree of differentiation of the keratinocytes. TLR2 expression is upregulated in inflammatory acne lesions and induced by C. acnes. The current study conducted to assess the oral isotretinion treatment effect on the acne vulgaris patients by evaluated the Toll Like Receptor 2 as a major immune system marker in Acne vulgaris immune response. Methods: 50 patients with acne vulgaris seen in outpatient clinic of dermatology centre(Al-Baidhaa out clinic center) in Baghdad during the period 1/9/2017 to 1/8/2018. The diagnosis of patients were done by the specialist dermatologist only sever and moderate acne cases were chosen. Fifty serum samples were collected before oral isotretinion therapy, only forty-five serum samples were collected after 8 weeks of oral isotretinion therapy. All patients have received 0.5mg-1mg/kg/day of oral isotretinoin. The mean ages was 22 years(range, 16-36 years). A total of 50 patients, 36(72%) of patients were females and 14(28%) were males. Furthermore 43(86%) of cases have heredity history. Also control serum samples were collected from people without acne and they chose with the same mean ages. The serum samples were stored at -70°C for up to six months. ELISA test for quantitative determination of TLR2 human was done. Statistical analysis was done using T-test. Results: Highly significant statistical difference were noticed (p<0.001) when we compare study group after therapy with control group, also highly significant statistical difference was noticed (p<0.01) when we compare study group before therapy with control group. Conclusion: Significant decrease of TLR-2 level was noticed in study group after isotretinoin therapy in comparison with same group before therapy and also with the control group. Pronouncedly the effects of oral isotretinion suggest a path towards importance of this therapy as an anti-acne agent